Image violation with the use of deepfake technology - a legal and practical analysis: Deepfake - protection of image - Bodanka, Oskar (The Opole Studies in Administration and Law, 2022)
The article presents considerations on the protection of image in the situation of violation by new technologies. The problem of image infringement in deepfake technology was discussed. The article presents what in the eyes of the law regulations deepfake is who is responsible for the image infringement made with the use of this technology and the paper presents currently functioning basic legal institutions of image protection. The author analysed of the existing sources of law, moreover in relation to the sources of law The Author was used dogmatic-legal method. He used this method by applying relevant provisions of private law, in particular civil law and copyright law, as well as referring to national jurisprudence and doctrinal views enabled a critical analysis of legal regulations in the context of protection of the right of publicity. The practical analysis of current legislation allows to point out fundamental doubts about the accuracy and correctness of the regulations adopted in this area. It was found that national laws, on the one hand, provide protection of the image from being captured and disseminated in deepfake materials, but on the other hand these regulations may cause serious doubts in doctrine and discrepancies in the interpretation of law. It has been pointed out that, regulations on image and AI technology in general should be regulated in detail by the legal system.